Adrenal crisis as a reversible etiology of heart failure with preserved ejection fraction: insights from a case series - Li, Mengmei; Shan, Ruicai; Song, Ling; Zhang, Chengsen (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAdrenal crisis, characterized by acute cortisol deficiency, is a rare, life-threatening condition that can precipitate cardiovascular collapse and heart failure (HF). Its role in HF with preserved ejection fraction (HFpEF) is underrecognized, particularly in cancer patients receiving therapies that impair adrenal function. This case series examines the clinical features, management, and outcomes of HFpEF induced by adrenal crisis, emphasizing early diagnosis and treatment.MethodsWe retrospectively analyzed four patients diagnosed with HFpEF secondary to adrenal crisis between January 2022 and January 2025 at Qingdao Central Hospital and Qingdao Municipal Hospital. Inclusion criteria included clinical evidence of adrenal crisis (low cortisol, hypotension, steroid responsiveness) and echocardiographic confirmation of HFpEF (EF ≥50%). Data on demographics, clinical presentation, laboratory findings, echocardiography, and outcomes were analyzed descriptively.ResultsThe cohort comprised three males and one female (aged 41–77 years), all with HFpEF (EF 50%–60%). Two presented with myocardial infarction (one NSTEMI, one STEMI), and two had malignancy with adrenal metastasis (renal, lung). Three exhibited hypotension. Initial BNP levels ranged from 518.93–619.13 pg/mL, decreasing to 108.06–287.63 pg/mL pre-discharge after hormone replacement therapy and HF management. Mean EF improved by 1.75% (range: 0%–3%) at one-month follow-up, with BNP further declining to 20.36–177.24 pg/mL. All patients achieved symptom resolution with no recurrence reported.ConclusionAdrenal crisis is a rare, reversible etiology of HFpEF in patients with diverse underlying conditions, potentially including those with cancer-related adrenal dysfunction or prior therapies. Prompt steroid therapy appears to improve cardiac function and outcomes, suggesting a need for heightened awareness and consideration of adrenal screening in at-risk populations, such as those with malignancy, tuberculosis, or other causes of adrenal insufficiency. Larger studies are needed to confirm these preliminary findings and establish the prevalence of this etiology across different subpopulations.